Does the corporate capital structure theory apply to banks? evidence from the field - Santos, Mário Coutinho dos (2021)
This paper investigates the value relevance of banks’ capital structure voluntary choices, their determinants, and preference in terms of funding mix policy models, using a unique survey-based dataset gathered through a faceto-face interview structured questionnaire, conducted to a sample of 51 Portuguese banks’ CEOs (89.5% survey response rate), over the 1989-1998 period. Survey participants, elicited ownership structure managerial control, growth opportunities, reputation in banking markets, financial flexibility, information signaling, bank size, share listing, business risk, dividend policy, and debt tax-shields, as the most relevant capital structure determinants at the bank level. The supervisory and regulatory discipline was indicated as the more influential external determinants for capital structure choice. A majority of 60 percent of state-owned bank CEOs declared a preference for following pre-determined guidelines on bank funding as capital structure policy model. Almost 53 percent of the privately-owned bank CEOs revealed a significant preference for the tradeoff capital structure policy model. The pecking order and the market-timing theories received moderate to weak preference. The paper extends the literature, providing field evidence that banking capital structure choice do matter and may be explained within the framework of the conventional corporate capital structure theory.